PROMIS Pediatric Anger Scale: an item response theory analysis. - Irwin DE; Stucky BD; Langer MM; Thissen D; Dewitt EM; Lai JS; Yeatts KB; Varni JW; Dewalt DA; Irwin, Debra E; Stucky, Brian D; Langer, Michelle M; et al. (Quality of Life Research, 2012)
Purpose: The Patient-Reported Outcomes Measurement Information System (PROMIS) aims to develop patient-reported outcome (PROs) instruments for use in clinical research. The PROMIS pediatrics (ages 8-17) project focuses on the development of PROs across several health domains (physical function, pain, fatigue, emotional distress, social role relationships, and asthma symptoms). The objective of the present study was to report on the psychometric properties of the PROMIS Pediatric Anger Scale.Methods: Participants (n = 759) were recruited from public school settings, hospital-based outpatient, and subspecialty pediatrics clinics. The anger items (k = 10) were administered on one test form. A hierarchical confirmatory factor analytic model (CFA) was conducted to evaluate scale dimensionality and local dependence. Item response theory (IRT) analyses were then used to finalize the item scale and short form.Results: CFA confirmed that the anger items are representative of a unidimensional scale, and items with local dependence were removed, resulting in a six-item short form. The IRT-scaled scores from summed scores and each score's conditional standard error were calculated for the new six-item PROMIS Pediatric Anger Scale.Conclusions: This study provides initial calibrations of the anger items and creates the PROMIS Pediatric Anger Scale, version 1.0.